Ekstrak Daun Pepaya dan Kangkung untuk Meningkatkan Daya Tetas Telur dan Kelangsungan Hidup Larva Lele (EXTRACTS OF CARICA PAPAYA AND IPOMOEA AQUATICA FOR IMPROVING EGG HATCHABILITY AND LARVAL VIABILITY OF CATFISH) - Saptiani, Gina; Hardi, Esti Handayani; Pebrianto, Catur Agus; Agustina, Agustina (Jurnal Veteriner; Vol 17 No 2 (2016), 2016)
This research was aimed to investigate the potential use of leaf extract of Carica papaya and Ipomoeaaquatica lto improve egg hatchability and larval viability of catfish. Dried leaves of Carica papaya andIpomoea aquatica were macerated and extracted in water and ethanol. Eggs and larvae were tested in theaquarium size of 10 L with a a diameter of 28 cm. The extracts in concentration 600, 800 and 1.000 ppmwere tested on the egg hatchability of catfish with immersion method, and challed with Aeromonashydrophyla, Pseudomonas sp., and Saprolegnia spp. The extracts in concentration 800 and 1.000 ppm weretested on the larval viability with immersion method, and challed with pathogens. Water or ethanolextract of Carica papaya and Ipomoea aquatica can improve egg hatchability 67±8% until 90±6% andlarval viability of catfish 77±0,5 until 90±9%. Eight hundred ppm ethanol extract of Carica papaya has thebest egg hatchability and 1000 ppm can improve larval viability of catfish.
Keywords: egg hatchability, larval viability, catfish, extract, C. papaya, I. aquatica